Tradable instruments to fight climate change: A disappointing outcome. (3rd March 2021) - Quirion, Philippe
Abstract: Various tradable instruments have been implemented for climate change mitigation: emission trading systems, tradable energy‐efficiency obligations, and tradable renewable energy quotas. Their track record has been disappointing so far; almost every emission trading has suffered from over‐allocation which has undermined its effectiveness; tradable energy‐efficiency obligations seem to have mostly co‐financed investments that would have taken place anyway; tradable renewable energy quotas suffer from several shortcomings compared to alternative support systems, that is, feed‐in tariffs and premiums. I discuss the reasons for these failures (especially too superficial a reading by policy makers of the work of researchers) and ways to improve the situation (including encouraging systematic syntheses of academic work). This article is categorized under: Climate Economics > Economics of Mitigation Abstract : Source: stock‐exchange‐4785086_1920. www.techeconomy2030.it. Licence CC BY‐NC‐SA 2.5